The impact of COVID-19 pandemic and distance learning on physical and mental health of Polish students - Mołoń, Mateusz; Janda, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. In Poland, on 25 March 2020, distance learning, which for many people was known only from literature, entered into force. As a result, education could no longer be provided in its current form and was therefore provided online. Therefore, the main aim of the presented research was an attempt to verify the pandemic and distance education impact on students psychophysical conditions and satisfaction. Material and methods. Some primary school students (grades 6th-8th), secondary school students from the Subcarpathian Voivodeship in Poland and also some university students from foreign countries completed an anonymous survey on the impact of the COVID-19 pandemic on their physical and mental condition as well as on some aspects of distance education. The research was conducted in December 2021 and 804 students (Primary and Secondary School) and 64 university students completed the survey. Results. Both the primary and the secondary school students claimed they were quite satisfied with distance education. The mostly approved aspect of online education was the fact that the time of learning was fitted to students’ needs. Difficulties in distance learning indicated by students were mainly connected with their mental health. Therefore, many students suffered from mental health and concentration problems, unwillingness to be active, apathy. The pandemic was also a stress factor for students and a reason why they were in a bad mood. The pandemic was the reason for an increased interest in natural sciences among 31.3% of primary school students, among 20.8% of secondary school students and among 17.3% of university students from foreign countries. Distance education influenced physical health of almost half of the respondents in both types of schools. The pandemic had an impact on mental health state of almost half of primary school students. 65% of secondary school students said that the pandemic influenced both their mental and physical health. In case of university students the pandemic did not influence their physical health in a significant way (65.4%). The study shows that primary school students used the Internet mainly to play games (almost 50% of the respondents), watch films, listen to music, do homework. Online lessons were only 20% of the answers. Conclusion. There has been a significant impact of COVID-19 on students in elementary school, high school, and university. This resulted in negative mental and physical effects. Respondents were stressed, depressed, and unmotivated. Approximately half of them engaged in physical activity very rarely or rarely. Even though they were satisfied with online learning, which was caused by the COVID-2019 pandemic, the greatest problem was mental concentration problems, lack of motivation, and social isolation.
Keywords: COVID-19; distance learning; e-learning; students